HUBUNGAN KARAKTERISTIK DAN PENGETAHUAN TENTANG LINGKUNGAN SEHAT DENGAN KEPUTUSAN KONSUMEN DALAM MEBELI SAYURAN ORGANIK DI CARREFOUR PLAZA MEDAN FAIR TAHUN 2013 - Rahma Fazrina; Irnawati Marsaulina; Evi Naria (Lingkungan dan Kesehatan Kerja, 2013)
The correlation of  the characteristics and the knowledge of environmental health with the consumers descision in purchasing the organic vegetables at Carrefour Medan Fair Plaza in year 2013. Vegetables are the most important food source which must be consumed everyday by the people due to the protein, vitamin, mineral and fiber which are so expedient for human’s body. In line with the development of science and technology which bring the people about the importance of the food ingredient’s quality for health and environmental sustainability. One of the effort which can be done is by consuming the organic vegetables. The aimed of this study was to describe the correlation of the characteristic, the knowledge of environmental health, the organic vegetables’ product, and the advantage of organic vegetables for health with the consumers decision in buying the organic vegetables at Carrefour Medan Fair Plaza 2013. This research was an analytical descriptive with Cross Sectional Study design. The research population was 8000 consumers who bought the organic vegetables at Carrefour Medan Fair Plaza with sample around 98 people. The research sample was taken by accidental sampling. The result of this research showed that the majority of respondent’s characteristic was at the age 19-44 years old (75,5%), whose income >Rp. 2.000.001 (82,7%), in line with the academic level (86,7%), and whose family members ≤ 4 people (82,7%) in a household. The analysis result was showing that there was no a significant correlation of the age variable (p=0,838) and the knowledge about environmental health (p=0,077) in line with the decision in buying the organic vegetables. In other hand, another research result was showing that there was a significant correlation of the income variable (p=0,016), the educational (p=0,006), the family members (p=0,035), the knowledge about the product (p=0,002), and the knowledge about the advantage of buying the organic vegetable for health (p=0,000) in line with the consumer decision in buying the organic vegetables. The consumer is expected to endure the consumption of organic vegetables and to increase the knowledge and the awareness of the importance of keeping the health and environmental by choosing the vegetables product. Keywords: Organic Vegetables, Knowledge, Purchase Decision